2008
DOI: 10.1007/s00467-008-0927-6
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 gene polymorphisms and primary vesicoureteral reflux in childhood

Abstract: The aim of this study was to assess the association between the transforming growth factor-beta1 (TGF-beta1) gene polymorphisms rs1800469 (commonly known as T-509C) and rs1982073 (commonly known as Leu (10)-->Pro) and primary vesicoureteral reflux (VUR) and renal scarring. Using a case-control approach, we examined 121 children with primary VUR and 169 controls. Genotyping of the TGF-beta1 gene polymorphisms was performed by restriction fragment length polymorphism (RFLP) analysis. The (99m)Tc-DMSA- or (99m)Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Valladares-Salgado et al 29 reported that TT genotype carriers of +869T/C polymorphism had lower cholesterol and triglycerides levels, and T allele carriers of +869 T/C polymorphism confer protection against diabetic nephropathy. Kowalewska-Pietrzak et al 30 reported that TT genotype carriers of À509 T/C polymorphism was a risk factor for renal scarring in primary vesicoureteral reflux (VUR), and was also associated with susceptibility to congenital uropathy. Yim et al 31 reported that TGF-b1 C-509T, G-800A, and T869C polymorphisms could be genetic markers of the process of urinary tract infection and VUR.…”
Section: Discussionmentioning
confidence: 99%
“…Valladares-Salgado et al 29 reported that TT genotype carriers of +869T/C polymorphism had lower cholesterol and triglycerides levels, and T allele carriers of +869 T/C polymorphism confer protection against diabetic nephropathy. Kowalewska-Pietrzak et al 30 reported that TT genotype carriers of À509 T/C polymorphism was a risk factor for renal scarring in primary vesicoureteral reflux (VUR), and was also associated with susceptibility to congenital uropathy. Yim et al 31 reported that TGF-b1 C-509T, G-800A, and T869C polymorphisms could be genetic markers of the process of urinary tract infection and VUR.…”
Section: Discussionmentioning
confidence: 99%
“…An association between polymorphism of angiotensin-converting enzyme gene and renal scarring was demonstrated (Haszon et al, 2002;Hohenfellner et al, 1999;Ohtomo et al, 2001;Ozen et al, 1999;Pardo et al, 2003). Similarly, polymorphism of transforming growth factor gene (Kowalewska-Pietrzak et al, 2008;Hussein et al, 2010) and polymorphism of vascular endothelium growth factor gene (Hussein et al, 2010) had impact on severity of renal scarring. Post-inflammatory nephropathy may be classified into reflux nephropathy due to vesicoureteral reflux and obstructive nephropathy due to urinary tract obstruction (Marra et al, 2004;Orikasa et al, 1995;Smellie et al, 1981).…”
Section: Urinary Tract Infections 310mentioning
confidence: 98%
“…Some studies questioned the significance of ACE gene polymorphism as an independent risk factor for the development and progression of RN (Dudley et al, 2002;Pardo et al, 2003). An association between TGF-1 gene polymorphism and the risk of renal scarring in patients with vesicoureteral reflux was also disclosed Kowalewska-Pietrzak et al (2008), whereas Hussein et al (2010) demonstrated an association between vascular endothelium growth factor (VEGF) gene polymorphism and the risk of the development of RN.…”
Section: Reflux Nephropathymentioning
confidence: 99%
“…The HWE was assessed in seven studies [38,39,42,43,46,50,51]. Calculation disclosed that seven studies presented a significant deviation from HWE [32,41,42,48,[51][52][53].…”
Section: Quality Of the Studiesmentioning
confidence: 99%
“…Most studies (67%) did not give a sufficient description of how they diagnosed UTIs in their patients, whereas six studies reported that the UTIs were diagnosed based on clinical and laboratory investigations [32,38,39,42,43,51].…”
Section: Quality Of the Studiesmentioning
confidence: 99%